Slow Infusion of Information Technology in Master Bank of Pakistan – A Case Study - Khalil, Fareeha; ., Muhammad Farhan (Information Management and Business Review, 2013)
E-Banking is now a well know phenomenon in the industry and amongst the banking users in Pakistan. This paper addresses the issues encountered and lessons derived by largest Pakistani bank while developing its e-banking capabilities. The paper explores some burning issues hindering key decisions of shifting to e-banking, e-banking delivery channel choice, enticing customers, and managing e-channel conflict to be made by bank. The findings indicated that the obstacles related to e banking customer location, customer satisfaction and the Bankâ€™s softwareâ€™s and communication infrastructure capabilities are influential factors in motivating the decision for shifting to a high-tech bank. The bank’s E-channel choice is influenced by competence of application and software technologies that the bank acquires and the nature of diffusion of information and communications among its stakeholders. Technological development in Banking practices and awareness in customers due to presence of foreign and domestic banks in Pakistani financial market influenced the Master Bank to switch over to complete automated banking system. The sophistication of ebanking services and the further rapid improvement appears to influence strategies to entice E-channel conflict issues. The paper concludes by suggesting the Bank to optimally utilize its resources by deploying efficient applications and softwareâ€™s and third party alliances and partnerships required to offer customized technology enabled banking services and develop appropriate e-banking risk mitigation strategies that bring the bank into a win-win position.